An assessment of public secondary school libraries in the division of city schools, Manila - Castillo, Kathleen N. (2004)
This study aimed to determine the strengths and weaknesses of the public secondary school libraries in the Division of City Schools, Manila and the extent of their compliance with the DECS Order Number 6 series of 1998, Policies and Programs for School Library Department.